Analyzing The Gender Differences in the Relationship Between Work from Home and Work-Life Balance During the Covid-19 Pandemic (Study on Teachers of Al-Azhar BSD Muslim Foundation, Indonesia) - Muhammad Daffa Al Rasyid; Andriyani Andriyani (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT With Covid-19 Pandemic that hits the world recently, offices need to be shut down due to the policy of government in order to curb the spread of the virus thus leaving all workers to work from home which includes teacher from the education sector, during this time the way people fulfil their work life balance changes when compared with the normal circumstances due to the new dynamic introduces when working from home such as all family members are stuck at home, the unavailability of domestic assistant, the lack of boundary between work and home, etc. However, it is predicted that a gender gap will emerge among workers with families given the sharp increase in housekeeping and childcare caused by the Covid-19 pandemic. Therefore, the objective of this study is to examine how gender differences affect the relationship between working from home and work life balance during the COVID-19 pandemic. Purposive sampling was used to choose the sample. By conducting an online survey to the teachers of Al Azhar BSD Muslim Foundation, data was gathered. 76 teachers with more than three years of teaching experience in total took part in this study. Hayes' PROCESSv4.1 was used to examine the data. The results of this study indicate that work from home has a significantly negative effect on work life balance, Meanwhile, Gender does not moderate the relationship between work from home and work life balance because given that men have started to participate more to housework in recent decades, both the male and female employees really divide their housework, with the males taking on more than their usual share due to working from home. Males in this position did not change their social behavior significantly, and they